Genetic analyses of isolated high‐grade pancreatic intraepithelial neoplasia (HG‐PanIN) reveal paucity of alterations in TP53 and SMAD4. Issue 1 (30th March 2017) - Hosoda, Waki; Chianchiano, Peter; Griffin, James F; Pittman, Meredith E; Brosens, Lodewijk AA; Noë, Michaël; Yu, Jun; Shindo, Koji; Suenaga, Masaya; Rezaee, Neda; Yonescu, Raluca; Ning, Yi; et al.
Abstract: High‐grade pancreatic intraepithelial neoplasia (HG‐PanIN) is the major precursor of pancreatic ductal adenocarcinoma (PDAC) and is an ideal target for early detection. To characterize pure HG‐PanIN, we analysed 23 isolated HG‐PanIN lesions occurring in the absence of PDAC. Whole‐exome sequencing of five of these HG‐PanIN lesions revealed a median of 33 somatic mutations per lesion, with a total of 318 mutated genes. Targeted next‐generation sequencing of 17 HG‐PanIN lesions identified KRAS mutations in 94% of the lesions. CDKN2A alterations occurred in six HG‐PanIN lesions, and RNF43 alterations in five. Mutations in TP53, GNAS, ARID1A, PIK3CA, and TGFBR2 were limited to one or two HG‐PanINs. No non‐synonymous mutations in SMAD4 were detected. Immunohistochemistry for p53 and SMAD4 proteins in 18 HG‐PanINs confirmed the paucity of alterations in these genes, with aberrant p53 labelling noted only in three lesions, two of which were found to be wild type in sequencing analyses. Sixteen adjacent LG‐PanIN lesions from ten patients were also sequenced using targeted sequencing. LG‐PanIN harboured KRAS mutations in 94% of the lesions; mutations in CDKN2A, TP53, and SMAD4 were not identified. These results suggest that inactivation of TP53 and SMAD4 are late genetic alterations, predominantly occurring in invasive PDAC. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.